Marketing Research of the Pharmaceutical Market of Restorative Action Drugs of the Republic of Uzbekistan - Azimov, A. A.; Maksudova, F. Kh.; Usmonova, M. K.; Yarkulova, Yu. M. (European Journal of Life Safety and Stability (2660-9630), 2021)
The analysis of the pharmaceutical market of restorative action drugs for 2019-2021 was carried out on the basis of the State Register of Medicines registered in the Republic of Uzbekistan. The structure of medicinal products by producer countries, origin, composition, and release forms has been studied. The main indicators and trends in the development of the range of medicines have been ascertained.